(untitled) (PAMPA, 2025)
The challenges posed by the intensive use of automobiles have become a recurring concern in urban planning practices. In the context of a paradigm shift in transport and mobility planning, this article analyzes the management of sustainable urban mobility in three medium-sized cities in Argentina’s Central Region (Córdoba, Santa Fe, and Paraná). The aim is to survey, systematize, and bring into dialogue the strategies, instruments, policies, and measures implemented in recent decades. Using a qualitative methodology based on documentary analysis of regulations, diagnoses, plans, and academic studies, the research identifies uneven progress, tensions between diagnosis and action, and gaps in institutional capacity and integrated planning. The results highlight innovative experiences, such as public bicycle systems and some attempts at metropolitan governance, alongside persistent problems related to public transportation and the absence of solid and stable regulatory frameworks.